Effects of Zakat and Government Debt on the Indonesian Economy - Annisa Munfaati; Heni Noviarita; Erike Anggraini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
In order to increase the country's economic growth, a stimulus is needed that can be used to detect whether there is an effect or not on changes in economic growth. As in the concept of modern economic growth which involves the role of household consumption and government expenditure. This thesis also uses the variable of state debt as a form of economic stimulus so that it will increase further and the distribution of zakat is also used as a driving factor for public consumption. This study aims to analyze whether there is an influence of zakat, consumption, state debt and government spending on economic growth in Indonesia for the period 2018-2020. The type of data used is secondary data obtained from BPS, BI, and the Ministry of Finance through published agency reports that were analyzed using multiple linear regression with the help of the E-Views 10 Program. The results of this study are the variables of zakat, consumption, state debt and government spending simultaneously have an effect on economic growth in Indonesia for the 2018-2020 period. The basic formulation of the philosophy of Islamic economic development includes the first Tawhid rububiyah, which states the basics of Allah's law to further regulate the development model based on Islam. Second, justice, namely development that is not lame (gaps), but equitable economic development (growth with equity). The third is the Khilafah, which states that humans are Allah's representatives on earth to prosper the earth and are responsible to Allah regarding the management of the resources entrusted to them. and lastly, Tazkiyah, which is to purify humans in their relationship with Allah, each other and the natural environment, society and country. Keyword : National Debt, Economy, Zakat